A bilirubin-derived nanomedicine attenuates the pathological cascade of pulmonary fibrosis. (August 2021) - Keum, Hyeongseop; Kim, Dohyeon; Kim, Jinjoo; Kim, Tae Woo; Whang, Chang-Hee; Jung, Wonsik; Jon, Sangyong
Abstract: Pulmonary fibrosis is an irreparable and life-threatening disease with only limited therapeutic options. The recent outbreak of COVID-19 has caused a sharp rise in the incidence of pulmonary fibrosis owing to SARS-CoV-2 infection-mediated acute respiratory distress syndrome (ARDS). The considerable oxidative damage caused by locally infiltrated immune cells plays a crucial role in ARDS, suggesting the potential use of antioxidative therapeutics. Here, we report the therapeutic potential of nanoparticles derived from the endogenous antioxidant and anti-inflammatory bile acid, bilirubin (BRNPs), in treating pulmonary fibrosis in a bleomycin-induced mouse model of the disease. Our results demonstrate that BRNPs can effectively reduce clinical signs in mice, as shown by histological, disease index evaluations, and detection of biomarkers. Our findings suggest that BRNPs, with their potent antioxidant and anti-inflammatory effects, long blood circulation half-life, and preferential accumulation at the inflamed site, are potentially a viable clinical option for preventing Covid-19 infection-associated pulmonary fibrosis.